Theoretical and numerical analysis on choked multiphase flows of gas and solid particle through a convergent–divergent nozzle. (March 2018) - Zhang, Guang; Kim, Heuy D
Particle–gas two-phase flows show significantly different behaviours compared to single-gas flow through a convergent–divergent nozzle. Non-equilibrium effects, thermal and velocity lags lead to the inefficiency of nozzle performance. In the present studies, theoretical analysis and numerical simulations were carried out to study particle–gas flows through a convergent–divergent nozzle. Homogeneous and equilibrium model that no slip in velocity and temperature occurs between particle phase and gas phase was considered to derive mass flow rate and sound speed of multiphase flows. Two-phase flows are regarded as isentropic flows that isentropic relations can be used for homogeneous equilibrium model. Particle volume fraction, specific heat ratio and gas constant parameter were also rewritten. Discrete phase model that includes Lagrangian-Eulerian tracking method was used to calculate particle–gas flows in computational fluid dynamics (CFD) studies. Particle mass loading was varied to investigate its effect on choking phenomena for particle–gas flows at different nozzle pressure ratios. Mass flow rate and sound speed of two-phase flows were theoretically calculated and compared with numerical results. Particle number density and particle velocity vectors were also obtained to explain particle motion through convergent–divergent nozzle.